Assessing the influence of human capital development on effective organizational performance; an investigation into the selected private higher education in Nangarhar, Afghanistan (Salam International Academic Journal, 2019)
Human resource developments are found to be one of the fundamental factors which contribute in the success of any organizations. In the context of the higher institutions sector, the importance and main purpose of the study is to establish the influence of human capital development on organizational performance, in specific within private educational sector of Nangarhar, Afghanistan. For completing this goal 6 higher educational institutions were selected, the study on hand used questionnaire for data collection, a total of 180 participant were viewed there thought, the findings of the study depict a strong and positive relationship between human capital development and organizational performance.
Keywords: Human Capital Development; Learning Capacity; Leadership Practices; Knowledge Accessibility